Effect of indigenous and non-indigenous arbuscular mycorrhizal fungi on growth, soil, fertility and plant nutrients uptake in Terung Asam (Solanum lasiocarpum Dunal) - Shahudin, Muhammad Akmal (2021)
erung asam (Solanum lasiocarpum Dunal) is a native fruit vegetable that is gaining interest as a commercial crop in Sarawak and Malaysia. Malaysia is covered by soils that are highly weathered, acidic and low in fertility and depend on chemical fertilizers to promote good plant growth. Alternative means to reduce dependency on chemical fertilizer e.g., arbuscular mycorrhizal fungi (AMF), must be sourced. Very little research on terung asam has been documented particularly on nutrient uptake. The objectives of this research were to: (i) determine the effect of indigenous and non-indigenous AMF on terung asam, (ii) investigate the effect of indigenous and non-indigenous AMF on soil fertility and nutrient uptake by terung asam, and (iii) evaluate colonization by indigenous and non-indigenous AMF on the root of terung asam. A greenhouse experiment was conducted using two indigenous AMF (T2 and T3), one non-indigenous AMF (T4) and one control (T1). The treatments were arranged in a complete randomized design with four subsamples and four replicates. Thirty-day-old seedlings were transplanted and measured for height, stem diameter, leaf chlorophyll for 90-days. Fresh and dry shoot and root weights were taken during harvesting. Plant nutrient analyses were conducted using Kjeldahl method for total N, single ashing for P and single ashing and double acid for K, Ca and Mg. Soil nutrients were extracted using Kjeldahl method for soil total N, aqua regia for total P, double acid for available P, aqua regia for total K, Ca and Mg and dilute double acid for exchangeable K, Ca and Mg. AMF root colonisation was conducted based on the gridline intersection method. Results revealed that the addition of AMF spores increased plant height by 13 to 33% and stem diameter by 5 to 25%. T4 plants showed dominance over T2 and T3. More leaves were retained by T4 plants at harvesting, an indication that the plant is stronger than other treatments. T4 recorded higher fresh shoot (11.27%) and dry shoot (14.98%) as well as fresh root (23.67%) and dry root (22.77%) weights than T1 plants. All potting media detected a decrease in total nutrient contents but increased in exchangeable K (88.55 to 158.88%), Ca (91.88 to 271.25%) and Mg (200.22 to 663.38%) were observed, with T2, T3 and T4 showing higher values than T1. Addition of AMF in treatments T2, T3 and T4 promoted better nutrient uptake by aboveground and belowground biomasses particularly for K, Ca and Mg. T4 was superior in terms of nutrient uptake for most nutrients. T3 recorded higher root colonisation (69.32%) followed by T4 (64.71%) with structures like arbuscules, vesicles and hyphae observed. AMF in T4 showed better results as the AMF spores are proven effective in promoting plant growth while AMF used in T2 and T3 were obtained from the field and untested. Indigenous AMF in T3 showed better results than T2 which could be related to the source of the inoculum. Finding of this study showed the potential of indigenous and non-indigenous AMF in promoting growth and nutrient uptake by terung asam plants.